Influence of user-generated content on destination loyalty among domestic millennials in Pulau Pangkor, Malaysia - Jamaludin, Mazlina (2018)
The travel and tourism industries are getting stronger and lucrative among tourism organisations and entrepreneurs. Domestic millennials travellers using the usergenerated contents (UGC) via the social media platforms are predominant. The present study is undertaken to examine the effects of destination loyalty among the domestic millennial travellers using the newly developed destination loyalty model. The study is guided by the theory of motivation on the ‘push and pull factors’ and the theory of satisfaction ‘expectancy disconfirmation’. The aim of the study is to fill the void between the casual relationships on UGC, visitors’ motivation, destination image, visitors’ satisfaction and destination loyalty. A structured questionnaire was developed using the comprehensive literature review, open-ended questions and short interviews. A pilot test was run for reliability and validity to ensure the questionnaire was appropriate before launching the actual survey. The actual data were collected at Dataran Jetty Pulau Pangkor, Malaysia from 246 domestic millennialss visitors, using purposive sampling via google form. All parameters were analysed by means of partial least squares via Smart PLS 3.0. Common method variances using Herman’s single factor test and marker variables were used. Result confirmed that there was no existence of biasness using the single-sourced data. The measurement model revealed that the construct reliability, convergent validity and discriminant validity were achieved according to the requirements. The structural (inner) model result showed that UGC was positively significant and had a direct relationship with visitors’ motivation, destination image and visitors’ satisfaction. Visitors’ motivation was positively significant and had a direct relationship with destination image and visitors’ satisfaction. The direct relationship between visitors' motivation and destination loyalty was positive but the relationship was insignificant. Destination images and visitors' satisfaction had direct, positive and significant relationship towards destination loyalty. The specific indirect effect of bootstrapping technique exhibited both mediating constructs which were destination image and visitors’ satisfaction which proved to be positively significant. The study suggested both H7 and H8 hypotheses were mediated between visitors’ motivation and destination loyalty. UGC and visitors’ motivation contributed 47.2% variance of destination image (R² = .472) and 40.4 % variance of visitors’ satisfaction (R² = .404), while UGC contributed a small portion of variance at 24.4% on visitors' motivation (R² = .244). The destination loyalty endogenous variable contributed 60.6% of variance from destination image, visitors’ satisfaction and visitors’ motivation (R² = .606) proving that the three constructs were very strong. This was due to the fact that destination image and visitors’ motivation were modelled as a higher order construct. The study made further advancement in travelling and tourism by presenting the casual relationship of the structural model using the partial least squares. The findings would assist destination managers on the social media UGC as a cost saver, while at the same time, cultivating positive mind-set among repeat visitors and future visitors to Pulau Pangkor. Furthermore, the millennials love sharing through UGC experience thus, extends their recommendation by sharing destination information to encourage repeat visits at low cost, and counter-acting any negative views. Furthermore, UGC can pin motivational interests through images, videos, audios and photographs which should create re-pins on the destination such as Pulau Pangkor. UGC con also be the primary marketing tools among the millennials to ensure effective and less costly at the destination. These efforts in matching specific needs and interests should garner higher visitors’ loyalty to any destination.